A contra-argumentação em discursos dos deputados federais no processo de impeachment da presidente Dilma Rousseff: um estudo semântico-argumentativo - Carvalho, Aleise Guimarães (2021)
The counter-argument is constantly understood as an answer to a previously exposed argumentation. It is often said that it is necessary to produce convincible discourses, in a way that they cannot be refuted. This is supported by the Rhetorical studies, which consider that the argumentation is elaborated by the speaker strategies and can be so strong that they can avoid counter-arguments, as well as they can be weak and provide the refuted answer. In an opposite perspective to the rhetoric, the TAL purposes that the counter-argumentation is linguistically marked, from certain expressions and phenomena (negation, operators and contraposition) that allow guiding the discourse in a contrary or opposed direction. On the basis of the studies developed by TAL, it aroused the interest of observing the construction of counter-argument in the political discourses, specifically, the discourses presented by the Federal Deputies during the impeachment discussion of the then president Dilma Rousseff, realized in 2016 April. Therefore, this study objectives to identify and analyse the semantic-argumentative phenomena, which cooperate with the construction of the counter-argumentation, registered in the tachygraphic notes of the Federal Deputies discourses, in the pronouncements sessions about the accusation of crime practiced by the president Dilma Rousseff, in order to understand the effects of sense resulting from the speaker behaviour before the produced utterances. For this purpose, the hypothesis of this research is that the counter-argumentation, in the “political discourse of parliamentary session” genre, manifests in a polyphonic manner, through the negation of contraposition operators, and these polyphonic constructions enable different semantic-argumentative behaviours of the speaker with relation to the utterances put on the scene. The investigation corpus of this research is composed of 438 (four hundred and thirty eight) political discourses that were published in 10 (ten) tachygraphic notes of the discussion sections about the accusations against the president Dilma Rousseff, in the Chamber of the Federal Deputies. Of this total, the study described and analysed the first 05 (five) sessions of the Federal Deputies discourses. The research methodology was quanta-qualitative, with descriptivist-interpretative nature, once it identified, quantitatively, the phenomena of contraposition, next, it described and analysed, interpreting them in the light of the Argumentative Semantics theory. The description and the analysis consider the theoretical contributions o Ducrot and collaborators (1984), Ducrot (1987 and 1988), Nascimento (2009), with respect to the studies of the Poliphony Theory, and Vogt and Ducrot (1980), Ducrot (1981), Koch (2011), Neves (2012 and 2013) and Silva (2010 and 2015), about the studies of the argumentative operators. In the face of the results observed in the developed research, five kinds of contraposition marks were verified that, more often, occurred in the investigated corpus. In addition, it was perceived that these different contraposition phenomena are realized together in the corpus and, thus, they contribute to the construction of the counter-argumentation in the “political discourse of parliamentary session” genre.